WANITA KARIR DAN PERANANNYA DALAM PENDIDIKAN ANAK: KAJIAN HUKUM KELUARGA ISLAM KONTEMPORER - Maryam Qurotul Aini, Siti; Alha Farisa (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Career women play a vital role in economic and social spheres, yet often face challenges in fulfilling their responsibilities in child education. This study analyzes the role of career women in parenting from the perspective of Islamic family law, including the impact of their careers on child development and Islamic solutions to address these challenges. Using a normative-descriptive method, the findings show that Islam permits women to work as long as their primary duties as mothers and wives are not neglected. Career demands—such as time constraints and reliance on caregivers—may affect a child’s emotional and spiritual growth. Islam offers solutions through shared parenting roles, time optimization, and the application of Islamic parenting principles that emphasize affection, moral values, and active parental involvement. With these strategies, career women can remain effective mothers while pursuing professional contributions.